Single-cell RNAseq profiling of early heart developmental physiology - Miranda, AMA; Tyser, RCV; Riley, PR; Scialdone, A; Marioni, J; Srinivas, S (Elsevier, 2017)
The heart is the first organ to form and function during mammalian development. Recently we established that in the mouse embryo, spontaneous asynchronous calcium oscillations (SACOs) occour in the cardiac crescent prior to the onset of cardiac contractions. Blocking Sodium Calcium Exchanger (NCX1) function inhibits these oscillations and cardiac differentiation.